Depresión y déficit neurocognitivo en adultos mayores de la parroquia San Pedro de Vilcabamba - Herrera Macas, Liliana Elizabeth (2023)
Depression and neurocognitive deficit in older adults accelerate the aging process, predisposing factors such as being a man over 60 years of age, living alone, having a low educational level, suffering from chronic diseases, having few financial resources, and presenting dependency for performing daily activities, increase the probability of presenting depressive symptoms, thus causing a decrease in their quality of life. The purpose of this study was to identify the presence of depression and neurocognitive impairment in the elderly of the San Pedro de Vilcabamba parish, according to sex and age group, and to establish the relationship between both variables. A quantitative, cross-sectional cohort approach was applied, with a sample of 77 participants, to whom the Yesavage scale (Depression Screening) and the miniCognitive Exam (MEC) were applied, obtaining as a result that the established depression was 28.6%, prevailing in men with 18.2% in the ages between 75-84 years. The presence of probable depression was 26.0%, predominantly in women aged 65-74 years with 7.8%. The presence of neurocognitive deficit was 61.0%, showing significance in men 65-74 years old. Of the established depression, it was evidenced that 16.9% of the older adults manifested mental deterioration. A p value of 0.913 was obtained, showing that there is no statistical relationship between the variables. In the present study it was found that depression is not linked to said deficit